Analisis Metafora dalam Lirik Lagu Karya Omoinotake - Ramadhan, Fitria Bakthi; Diner, Lispridona (KIRYOKU, 2025)
This study was conducted to discover the types and meanings of metaphors contained in the lyrics of Omoinotake's songs. This study aims to identify the types of metaphors and describe their meanings based on the theories of Ullman and Knowles & Moon. The research objects are the five songs by Omoinotake with the highest number of views on YouTube Music as of 2025. This study was structured based on an objective approach and data were collected through listening and note-taking techniques. Data analysis was conducted using descriptive methods. The results of this study found a total 47 metaphorical data. Based on the results of the study, abstraction metaphors are the most frequently found type of metaphor, while animal and synesthetic metaphors are the least frequently found types. The most frequently found abstraction metaphors show songwriters depicting abstract concepts in a concrete and aesthetic way, so that they can make song lyrics more beautiful and attract song listeners.